The Clinical Correlation of the Hart-ISSG Proximal Junctional Kyphosis Severity Scale With Health-Related Quality-of-life Outcomes and Need for Revision Surgery. Issue 3 (February 2016) - Lau, Darryl; Funao, Haruki; Clark, Aaron J.; Nicholls, Fred; Smith, Justin; Bess, Shay; Shaffrey, Chris; Schwab, Frank J.; Lafage, Virginie; Deviren, Vedat; Hart, Robert; Kebaish, Khaled M.; et al.
Abstract : Study Design: Retrospective analysis of prospective data. Objective: Evaluate the utility of the Hart-International Spine Study Group proximal junctional kyphosis severity scale (Hart-ISSG PJKSS). Summary of Background Data: Proximal junctional kyphosis (PJK) and failure (PJF) are well-described complications after long-segment instrumentation. The Hart-ISSG PJKSS was recently developed and incorporates neurological deficit, pain, instrumentation issues, degree of kyphosis, presence of fracture, and level of upper-most instrumented vertebrae. Methods: All adult spinal deformity patients with PJK or PJF were identified from two academic centers over a 7-year period. Health-related quality-of-life (HRQOL) outcomes were prospectively collected: Oswestry Disability Index (ODI), visual analogue scale (VAS) pain, SF-36 questionnaire, and SRS-30 questionnaire. Patients were retrospectively assigned Hart-ISSG PJKSS scores. Correlation between the Hart-ISSG PJKSS and outcomes was assessed with linear regression, Pearson correlation coefficients, and χ 2 analysis. Results: A total of 184 cases were included; 21.2% were men and mean age was 65.0 years. Weakness and/or myelopathy were present in 11.4% of patients and 88.6% had pain. Instrumentation issues occurred in 44.0% and 64.1% had PJK-associated fractures. PJK occurred in the upper thoracic spine in 21.7% of cases. Mean PJKSS score was 5.9. The Hart-ISSG PJKSS was significantly and strongly associated with ODI ( P  < 0.001, r  = 0.611), VAS pain ( P  < 0.001, r  = 0.676), SRS-30 function ( P  < 0.001, r  = −0.401), SRS-30 mental health ( P  < 0.001, r  = −0.592), SRS-30 self-image ( P  < 0.001, r  = −0.511), SRS-30 satisfaction ( P  < 0.001, r  = −0.531), and SRS-30 pain ( P  < 0.001, r  = −0.445). Higher scores were associated with higher proportion of patients undergoing revision surgery ( P  < 0.001); scores of 9 to 11 and 12 to 15 underwent revision 96.0% and 100.0% of the time, respectively. Conclusion: The Hart-ISSG PJKSS was strongly correlated with validated functional outcomes and higher scores were associated with higher rates of revision surgery. The Hart-ISSG PJKSS may be a useful clinical tool in the treatment of patient with PJK. Level of Evidence: 3